2005
DOI: 10.1111/j.1740-0929.2005.00251.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of theanine, γ‐glutamylethylamide, on bodyweight and fat accumulation in mice

Abstract: To clarify the details of the anti-obesity effect of theanine, g -glutamylethylamide, female ICR mice were fed diets containing theanine at the concentrations of 0.01, 0.02, 0.04, 0.08 and 0.16% for 16 weeks. Bodyweight and food intake in the mice were measured every 4 weeks, and several organs and intraperitoneal adipose tissues (IPAT) were weighed after the feeding. In addition, lipid levels in the serum and liver were analyzed. As a result, the bodyweight increase and weight of IPAT were significantly reduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(32 citation statements)
references
References 19 publications
1
29
0
Order By: Relevance
“…Moreover, ICR mice are outbred and genetically heterogeneous mice, which are commonly not used for studies in obesity research. Additionally, it appears that the mice were fed a regular, low-fat diet, which in most mouse models does not lead to the development of obesity, especially when given at a young age as in the described study [50]. Therefore, the animal model chosen in this study might not be appropriate for investigation of anti-obesity effects.…”
Section: Anti-obesity Effects Of Green Teamentioning
confidence: 89%
See 1 more Smart Citation
“…Moreover, ICR mice are outbred and genetically heterogeneous mice, which are commonly not used for studies in obesity research. Additionally, it appears that the mice were fed a regular, low-fat diet, which in most mouse models does not lead to the development of obesity, especially when given at a young age as in the described study [50]. Therefore, the animal model chosen in this study might not be appropriate for investigation of anti-obesity effects.…”
Section: Anti-obesity Effects Of Green Teamentioning
confidence: 89%
“…In ICR mice, the effects of different green tea components were investigated [50]. Caffeine and theanine suppressed body weight and body fat, while catechins did not change these parameters but reduced serum triglycerides and free fatty acids.…”
Section: Anti-obesity Effects Of Green Teamentioning
confidence: 99%
“…At 100 lM, EGCG also inhibited the activity of two other cholesterol-biosynthetic enzymes, lanosterol 14a-demethylase and oxidosqualene:lanosterol cyclase [68]. Together with the inhibition of micelle formation [56] and the stimulation of fecal cholesterol excretion [32,38] by EGCG as discussed in Section 3.1, EGCG's inhibition of cholesterol-biosynthetic enzymes may be related to the low plasma cholesterol levels observed in rats IP-injected with EGCG [18]. Interestingly, an in vivo study [69] shows that no effect of green tea on the activity of HMG-CoA reductase and cholesterol 7a-hydroxylase was observed, suggesting the selective effect of green tea or EGCG on the cholesterol-biosynthetic enzymes.…”
Section: Inhibition Of Lipogenic Enzymesmentioning
confidence: 90%
“…Caffeine has been demonstrated to reduce the weight of adipose tissues in experimental animals (Hasegawa and Mori, 2000;Zheng et al, 2004). Kobayashi-Hattori et al (2005) have shown that the intake of caffeine elevated the serum level of catecholamine in rats fed a high fat diet, and they presumed that the enhancement of the production of catecholamine accelerated lipolysis.…”
Section: Cumulationmentioning
confidence: 99%
“…Raw green coffee beans, which are materials of coffee, are rich in caffeine, chlorogenic acid, and its related components, such as quinic acid, caffeic acid, and p-coumaric acid. Caffeine has been reported to promote lipolysis in adipocytes of experimental animals and humans (Hasegawa and Mori, 2000;Zheng et al, 2004;LopezGarcia et al, 2006). Kobayashi-Hattori et al (2005) has observed that caffeine reduced body fat mass and body fat percentage in a dose-dependent manner in rats fed high-fat diets.…”
Section: Introductionmentioning
confidence: 99%